The New Mindset for Leading Effectively in Collaborative Ecosystems - Cotrim, J.; Além, F. (Revista de Governança Corporativa, Compliance e Negócios Sustentáveis, 2021)
The world has been witnessing the emergence of what some call a new paradigm of collaborative ecosystems (CEs), more holistically known by some as sharing economy (SE), over the last decade or so. Such a phenomenon has been having disruptive effects, namely, on the reshaping of economies and societies. On the other hand, the current dramatic environmental, socio-economic and political instability across the globe has been instigating many observers, academics, and practitioners to question not only the reasons for such crisis but, most importantly, how one should tackle today’s challenging times. One of the answers for that question has been put forward by some prominent analysts: there seems to be a misalignment between the current status quo in leadership (political and management) and the new demands the present world is asking for. Change, therefore, is needed, if one wants to construct a Greener Model for all stakeholders involved. But what kind of change is, exactly, entailed? We advocate that there must be a new mentality centered around developing a social-emotional mindset of collaboration in leaders (being corporate or political). With the increase of CEs, leaders must inevitably become team players, develop and improve their flexibility, share their ideas, and develop their sensemaking, all in a collaborative environment. We call this a collaborative social-emotional Bio-leadership mindset.